NaviCane / Nur Saadah Ibrahim … [et al.] - Ibrahim, Nur Saadah; Anuar, Nur Nafiezsya Airienna; Mohd Fadli, Nur Shafiqah; Abdul Rahim, Najihah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
People who are disabled, either by birth or accident, experience physical or mental limitations that make it difficult for them to fully enjoy life. Technology offers various tools to assist them in their daily lives. Kayou Enterprise introduces smart canes to assist people with vision impairments become independent. These canes offer features such as sensor technology that has sound aids to alert users of obstacles in their path when detecting obstacles and reflectors for safe navigation. The existence of a reflector on this cane is for safety concerns for the user to avoid any accidents. Other than that, obstacles can range from small items on the ground to larger objects like furniture or vehicles. The cane must be sensitive enough to detect these obstacles without false alarms. Our canes feature a button mechanism for easy extension and retraction, unlike traditional sticks, making them user-friendly as they only require a single press to operate. A telescope's shape inspires Kayou Enterprise's cane. The cane's distinctive design encourages the user to use it more fashionably and ergonomically. We use the TikTok platform to post videos using FYP hashtags so that people can easily find our videos. Our videos showcase the functionality and durability of our canes, helping potential customers make informed decisions. Not to mention, we plan to paint the cane's body parts using reflective paint to simplify the production process. The reflective paint will also enhance visibility for users in low-light conditions, adding an extra layer of safety.